Optimization of Piper Trilinier Diagram Using Lithium Isotope Systematics: An Application for Detecting the Contribution of Geothermal Water from Aso Caldera after Earthquake 2016 in Kumamoto Aquifer, Japan (Indonesian Journal of Science and Technology, 2025)
Optimization of the use of the Piper trilinear diagram was carried out by adding Lithium isotope systematics as a more accurate water-type analysis. The method used in this research is to analyze the Cl/Li ratio > 1000, δ7Li < 10 ‰, and Lithium concentration of groundwater, and then the results of the analysis are integrated into a Piper trilinear diagram. The research results show that Lithium isotope systematics (Cl/Li ratio < 1000, δ7Li < 10 ‰ and Li concentration) graph can be divided into 3 regions, namely geothermal water type has Cl/Li < 1000 and δ7Li < 10 ‰, then shallow groundwater which has Cl/Li > 1000 but δ7Li < 10 ‰ experienced natural contamination from geothermal waters, and fluid that has a Cl/Li ratio > 1000 and 10 ‰ > δ7Li > 20 ‰ is estimated to be shallow groundwater.
Keywords: Optimization; Geothermal waters; Lithium isotope systematics; Piper trilinear diagram; Shallow groundwater; Water type analysis